(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
The article is devoted to the analysis of the flora of higher plants distributed on the territory of the Kulun-Ata State Reserve. The purpose of the study is to analyze and evaluate the knowledge of higher plants of the specified reserve.As a result of the analysis of the flora, it was established that it is rich in species composition, although the taxonomic categories are given according to old sources, the result of which is that the names of some taxa do not correspond to modern classifications. According to literary sources, about 394 species of higher plants belonging to 83 families from 3 divisions are found on the territory of the reserve.